"We do investigate ourselves": figurative assessment practices as meaning-making in English education. Issue 2 (2nd April 2020) - Jarvie, Scott; Beymer, Alecia
ABSTRACT: In this study of microteaching in a secondary English methods course, we intentionally stray from normative assessment practice, instead asking pre-service teachers to provide feedback on their peers' microteaching using assessment practices designed to orient them figuratively . The term 'figurative' refers to 'figurative language': the bringing together of multiple, seemingly unrelated things, through associative configurations, and placing them side-by-side in order to reorient thought towards new or unexpected meanings. This study reframes assessment, not as a means of collecting data on what students have learned from a given lesson in order to evaluate and augment learning, but instead figuratively, as providing opportunities to expand and imagine ways of meaning-making through and with assessment. We examine in detail four modes of figurative assessment practices through which we sought to surprise and disorient students, producing new and different kinds of responses to microteaching that went beyond normative feedback practices.